2022
DOI: 10.1101/2022.06.09.22275139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

European Fitness Landscape in Children and Adolescents: updated reference values, fitness maps, and country rankings based on nearly 8 million data points from 34 countries gathered by the FitBack network

Abstract: Objectives: (1) To develop reference values for health-related fitness European children and adolescents aged 6-18 years that are the foundation for the web-based, open-access and multi-language fitness platform (FitBack); (2) To provide comparisons across European countries. Methods: This study builds on a previous large fitness reference study in European youth by: (1) widening the age demographic, (2) identifying the most recent and representative country-level data, and (3) including national data from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…5,6,[19][20][21][22] If this is true, and can be verified by future causal analysis, the potential of public health initiatives targeting cardiorespiratory fitness or physical activity to reduce cancer mortality might be underappreciated. 49,50 This study also revealed a heterogeneous pattern regarding adolescent cardiorespiratory fitness and site-specific cancer after comparing full siblings. For example, 13 the associations showing lower risks of kidney and liver, bile ducts, and gallbladder cancer seemed to attenuate more, whereas those with colon and head and neck cancer seemed more robust.…”
Section: Comparisons With Other Studiesmentioning
confidence: 68%
“…5,6,[19][20][21][22] If this is true, and can be verified by future causal analysis, the potential of public health initiatives targeting cardiorespiratory fitness or physical activity to reduce cancer mortality might be underappreciated. 49,50 This study also revealed a heterogeneous pattern regarding adolescent cardiorespiratory fitness and site-specific cancer after comparing full siblings. For example, 13 the associations showing lower risks of kidney and liver, bile ducts, and gallbladder cancer seemed to attenuate more, whereas those with colon and head and neck cancer seemed more robust.…”
Section: Comparisons With Other Studiesmentioning
confidence: 68%
“…From the point of view of public health, education and sport, the development and implementation of PF tests seems to be justified [ 23 , 24 , 27 , 28 , 29 ]. Despite well-documented benefits stemming from higher PF levels in youth, there is an ongoing debate whether its levels in young people gradually decrease with age [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to interpret results of such a test properly, it is necessary to have accurately calculated reference norms [ 21 ]. Therefore, different batteries of tests assessing selected components of PF related to health, sports skills or aptitudes of adolescents were developed [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%